A study on customers’ satisfaction towards services provided by agency at Urban Transformation Center (UTC) Melaka / Muhd Lokman Nul Hakim Lamri - Lamri, Muhd Lokman Nul Hakim (Faculty of Business and Management, 2014)
The main objective of this study was to study the level of customer satisfaction towards service provided by agency at UTC Melaka through the service quality model developed by Parasuraman which tangibility, reliability, responsiveness, empathy and assurance. The instrument used to study the level of customer satisfaction was questionnaires which were distributed to 110 respondents at UTC Melaka. The sampling for this study was non-probability due to this study was carried out at public and the researcher did not get the exact population of customers that came to UTC Melaka. The researcher used convenient sampling to distribute questionnaire which the researcher approached the customers randomly at five agencies in UTC Melaka. The result was analyzed by using SPSS version 20.0 and there were two analyses used which were descriptive statistics; to find the level of customer satisfaction using mean and Pearson correlation to find the relationship between service quality (tangibility, reliability, responsiveness, assurance and empathy) and customer satisfaction. The findings showed that the level of customer satisfaction towards service provided by agency at UTC Melaka was high which 3.6588. All the studied factors indicated significant relationship with customer satisfaction. The value of r for tangibility was 0.450, reliability (0.558), responsiveness (0.457), assurance (0.313), and empathy (0.475). As a conclusion customer satisfied with the service provided by agency at UTC Melaka and reliability was the most factor that affect the customer satisfaction.